Physiologically based pharmacokinetic modelling and simulation to predict the plasma concentration profile of schaftoside after oral administration of total flavonoids of Desmodium styracifolium - Li, Xue; Chen, Chao; Ding, Nan; Zhang, Tianjiao; Zheng, Peiyong; Yang, Ming (Frontiers in Pharmacology, 2022)
Introduction: The total flavonoids of Desmodium styracifolium (TFDS) are the flavonoid extracts purified from Desmodii Styracifolii Herba. The capsule of TFDS was approved for the treatment of urolithiasis by NMPA in 2022. Schaftoside is the representative compound of TFDS that possesses antilithic and antioxidant effects. The aim of this study was to develop a physiologically based pharmacokinetic (PBPK) model of schaftoside to simulate its plasma concentration profile in rat and human after oral administration of TFDS. Methods: The PBPK model of schaftoside was firstly developed and verified by the pharmacokinetic data in rats following intravenous injection and oral administration of TFDS. Then the PBPK model was extrapolated to human with PK-Sim® software. In order to assess the accuracy of the extrapolation, a preliminary multiple-dose clinical study was performed in four healthy volunteers aged 18-45 years old. The predictive performance of PBPK model was mainly evaluated by visual predictive checks and fold error of Cmax and AUC0-t of schaftoside (the ratio of predicted to observed). Finally, the adult PBPK model was scaled to several subpopulations including elderly and renally impaired patients. Results: Schaftoside underwent poor metabolism in rat and human liver microsomes in vitro, and in vivo it was extensively excreted into urine and bile as an unchanged form. By utilizing literature and experimental data, the PBPK model of schaftoside was well established in rat and human. The predicted plasma concentration profiles of schaftoside were consistent with the corresponding observed data, and the fold error values were within the 2-fold acceptance criterion. No significant pharmacokinetic differences were observed after extrapolation from adult (18-40 years old) to elderly populations (71-80 years) in PK-Sim®. However, the plasma concentration of schaftoside was predicted to be much higher in renally impaired patients. The maximum steady-state plasma concentrations in patients with chronic kidney disease stage 3, 4 and 5 were 3.41, 12.32 and 23.77 times higher, respectively, than those in healthy people. Conclusion: The established PBPK model of schaftoside provided useful insight for dose selection of TFDS in different populations. This study provided a feasible way for the assessment of efficacy and safety of herbal medicines.